ANALYZING THE IMPORTANCE LEVEL AND SERVICE PERFORMANCE OF AUTOMATED TELLER MACHINE (ATM) OF MANDIRI BANK - Lenny Setiawati; Toto Sugiharto (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The study was aimed at analyzing the importance and service performance of Automated Teller Machine (ATM) of Mandiri Bank. Servqual Analysis consisting of tangible, reliability, responsiveness, assurance, and empathy dimensions, was applied to analyze ATM performance quality. Meanwhile, Customer Satisfaction Index and Importance Performance Analysis which consists of quadrant analysis and gap analysis were used respectively to analyze overall customer satisfaction and to identify performance of dimensions needing improvement. Data were gathered using questionnaires from 100 respondents who were randomly selected. Results of the study showed that customers were satisfied by the bank ATM overall service quality and performances. This was indicated by customer satisfaction index of 80.93. It was also found that assurance was identified as the most important dimension of service quality which needs improvement due to its performance which was below customers’ expectation. Reliability, on the other hand, was found as dimension of service quality whose performance was also below customers’ expectation. Since it was regarded as less important than assurance, its improvement priority was lower than that of assurance. Other dimensions of service quality, according to their improvement priorities, were empathy, responsiveness, and tangible, respectively.Key words: Automated Teller Machine (ATM); customer satisfaction; tangible; reliability; responsiveness; assurance; emphaty; Servqual; Importance Performance Analysis; Customer Satisfaction Index.